Visualizing renal primary cilia. Issue 3 (25th February 2013) - Deane, James A; Verghese, Elizabeth; Martelotto, Luciano G; Cain, Jason E; Galtseva, Alya; Rosenblum, Norman D; Watkins, D Neil; Ricardo, Sharon D
Abstract Renal primary cilia are microscopic sensory organelles found on the apical surface of epithelial cells of the nephron and collecting duct. They are based upon a microtubular cytoskeleton, bounded by a specialized membrane, and contain an array of proteins that facilitate their assembly, maintenance and function. Cilium‐based signalling is important for the control of epithelial differentiation and has been implicated in the pathogenesis of various cystic kidney diseases and in renal repair. As such, visualizing renal primary cilia and understanding their composition has become an essential component of many studies of inherited kidney disease and mechanisms of epithelial regeneration. Primary cilia were initially identified in the kidney using electron microscopy and this remains a useful technique for the high resolution examination of these organelles. New reagents and techniques now also allow the structure and composition of primary cilia to be analysed in detail using fluorescence microscopy. Primary cilia can be imaged in situ in sections of kidney, and many renal‐derived cell lines produce primary cilia in culture providing a simplified and accessible system in which to investigate these organelles. Here we outline microscopy‐based techniques commonly used for studying renal primary cilia.